Improving Descriptive Writing Through Picture Series in Grade IV: Meningkatkan Kemampuan Menulis Deskriptif Melalui Seri Gambar di Kelas IV - Sholicha, Amilatus; Setiyawan, Enik (Indonesian Journal of Education Methods Development, 2025)
Background: Writing descriptive text remains challenging for many elementary students due to limited vocabulary mastery and difficulties generating ideas. Specific Background: The lack of engaging media in writing lessons often results in low motivation and poor writing structure. Knowledge Gap: Few studies explore the use of picture series in supporting structured descriptive writing within the context of Grade IV students in this school. Aim: This study aims to improve students’ descriptive writing skills through the use of picture series. Methods: This classroom action research consisted of two cycles involving planning, action, observation, and reflection. Data were collected through writing tests, observation sheets, and documentation. Results: Students’ writing improved in content, organization, vocabulary, and mechanics across cycles, showing steady progress from the initial baseline to the final cycle. Novelty: This study presents a contextualized application of picture series tailored to the characteristics of Grade IV learners. Implications: Picture series can serve as an accessible and effective visual tool to support structured descriptive writing in elementary classrooms. Highlights:• Picture series improved students’ descriptive writing structure• Increased vocabulary use and idea development• Higher motivation observed during visual-based learning Keywords: Picture Series, Descriptive Writing, Elementary Students, Writing Skills, Visual Media